A phase 1b randomised clinical trial evaluating BBI-001, a non-absorbed oral therapeutic for the treatment of iron overload - Curtis Scribner; Jamie Cope; Philip Ryan; John K. Olynyk; John Ryan; J. Daniel Griffin; Cory Berkland (Scientific Reports)
Abstract Non-transfusion-dependent iron overload is the result of excessive dietary iron absorption, most commonly caused in populations of European descent by the genetic disorder HFE-related hemochromatosis (HH). In this disorder, hyperabsorption of 3–5 mg of iron per day cannot be counterbalanced by the typical passive elimination of 1–2 mg of iron each day into the feces by the shedding of enterocytes. Therefore, the current standard of care for most HH individuals who develop iron overload is to undergo systemic iron reduction with induction-phase phlebotomy therapy followed by long-term maintenance phlebotomy therapy. Unfortunately, long-term compliance with a regular phlebotomy regimen is less than 25% in some clinical settings. BBI-001 is a non-absorbed, oral therapeutic that binds dietary iron in the gut, preventing absorption and promoting iron elimination in the feces. The safety and efficacy of BBI-001 was confirmed in a single ascending dose, double-blind, Phase 1b clinical trial NCT05238207 (14/02/2022) in patients with iron deficiency. No treatment-related adverse events occurred for single doses of up to 2000 mg of BBI-001. The study also established proof-of-mechanism since BBI-001 significantly reduced the absorption of iron isotopes from breakfast meals compared to placebo. BBI-001 was most effective in subjects who hyperabsorbed iron (> 3 mg) on placebo, suggesting an ability to normalize iron absorption in at-risk patients. This study supports the further evaluation of BBI-001 as a safe pharmaceutical alternative to lifelong therapeutic phlebotomy.